NGMA-2. Dual sgRNA-directed PD-L1 knockout in human glioblastoma cells using the CRISPR/Cas9 system. (5th July 2021) - Fierro, Javier; Dipasquale, Jake; Aguilar, Rocio; Perez, Joshua; Tran, An; Factoriza, Chris; Dou, Huanyu
Abstract: Glioblastoma multiforme (GBM) is an astrocyte derived brain tumor. It induces an immunosuppressive microenvironment by exploiting immune checkpoints such as the PD-1/PD-L1 pathway. Targeting the PD-1/PD-L1 pathway for immunotherapy is a promising new avenue for treating GBM, but more work is needed to develop a safe and effective method for clinical applications. We identified two sgRNA sequences located on PD-L1 exon 3. The first sgRNA recognized the forward strand of human PD-L1 near the beginning of exon 3 and cuts at approximately base pair 82 (g82). The second sgRNA recognized the reverse strand of exon 3 and cuts at base pair 165 (g165). Two sgRNAs, g82 and g165, created an 83bp deletion in the genomic sequence that can lead to the production of a non-functional PD-L1 protein. A homology-directed repair template (HDR) containing an in-frame stop codon was designed to enhance PD-L1 knockout specificity and efficiency. Both g82 and g165 were cloned into the CRISPR/Cas9 plasmid, and was co-transfected with the added HDR template. T7E1, qRT-PCR and western blot analysis determined that the dual sgRNA CRISPR/Ca9 system knocked out both endogenous (80%) and exogenous (64%) PD-L1 in U87 cells and PD-L1 overexpression U87 cells, respectively. Deletion of PD-L1 reduced U87 migration and proliferation, while PD-L1 overexpression promoted tumor growth and tumor-associated macrophage polarization. Together, deletion of both membrane and cytoplasmic PD-L1 altered the PD-L1-associated immunosuppressive environment and prevented tumor progression and migration. Thus, a dual sgRNA CRISPR/Cas9 gene-editing system is a promising avenue for anti-GBM immunotherapy.